Sérieuse, audacieuse, bienheureuse... Généreuses! Rencontre avec Isabelle Panneton, Marie Pelletier et Ana Sokolovic - Davoine, Françoise (Circuit : musiques contemporaines, 1999)
In this exchange with three women composers, Françoise Davoine draws a portrait of their risks, anguish and preoccupations. The speaking-style of the text has been preserved here, giving freshness to the statements as each woman talks about her situation, and the creative process, etc.

Ana Sokolovic : entrevue avec Jean Lesage - Lesage, Jean (Présence de la musique québécoise. Vingt-deux portraits instantanés, 1999)

À propos de cinq œuvres symphoniques de Linda Bouchard - Nattiez, Jean-Jacques (Présence de la musique québécoise. Vingt-deux portraits instantanés, 1999)

Isabelle Panneton : à contretemps - Panneton, Isabelle (Présence de la musique québécoise. Vingt-deux portraits instantanés, 1999)

Estelle Lemire : portrait de l'artiste-compositeure - Provost, Serge (Présence de la musique québécoise. Vingt-deux portraits instantanés, 1999)

Maureen Forrester: Canada's Charming Contralto :a Biography for Young People - Roy, Lynette (Orchid Communications, 1999)

Linda Bouchard : la musique de Linda Bouchard - Tourigny, Maurice (Présence de la musique québécoise. Vingt-deux portraits instantanés, 1999)

Dr. Violet Balestreri Archer, Her Life, Her Vocal Literature, and Her Influence on Contemporary Canadian Music - Valente, Liana Elsie (Université de Caroline du Sud, 1999)
Keywords: Pas de lien web